Antifungal Activity of Triterpenoids and Steroids Isolated from Pinus merkusii Bark Against Phanerochaete chrysosporium - Masendra Masendra; Brandon Arsito Verick Purba; Ganis Lukmandaru (Wood Research Journal, 2020)
The outer part of a tree, known as the bark, protects the internal tissues from external conditions and attacks from microorganisms. Its antifungal activities are due to the presence of chemicals in this bark. This study aimed at evaluating the toxicity of triterpenoids and steroids from the bark of Pinus merkusii against Phanerochaete chrysosporium (white-rot). The triterpenoids and steroids were isolated from n-hexane extract of the bark through column chromatography. Then, the antifungal activity was evaluated by measuring the growth rate of the fungus on potato dextrose agar (PDA) medium in a Petri dish. The isolation resulted in three triterpenoids (3β- methoxyserratt-14-en-21-one, serrate-14-en-3β,21β –diol, 3α,21β- dimethoxy-D14-serratene) and two steroids (β-sitosterol, Stigmast-4-en-3-one). There was more of antifungal activity with β-sitosterol and serrate-14-en-3β,21β –diol, due to presence of hydroxyl bond and their hydrophobicity.